Corporate social responsibility and HIV/AIDS prevention at Sechaba Brewery Holdings Limited - Tekere, Mooketsi Bennedict (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MPhil)--University of Stellenbosch, 2011.